Hubungan Ketuban Pecah Dini Dengan Kejadian Leukositosis Bayi Baru Lahir Pada Persalinan Sectio Caesarea - Nisa, Faraidyah Ayu; Hanifah, Iis; Wahyuningsih, Sri (Universitas Islam Jember, 2025)
One of the main causes of maternal and infant mortality in Indonesia is infection. Infection in the mother can occur due to premature rupture of membranes which can increase the risk of infection. Neonatal sepsis can cause leukocytosis (an increase in the number of white blood cells or leukocytes) in infants, which is an indicator of infection in response to bacterial infection in the body. This study aims to determine the relationship between premature rupture of membranes and the incidence of leukocytosis in newborns during Caesarean section delivery. This study is an observational analytical study with a retrospective approach. The data collected were secondary data from patient medical records from January to December 2024. Respondents were taken using a total sampling technique of 75 respondents, the test used was the Chi Square Test. The analysis results obtained a p value = 0.006, <α = 0.05 which indicates a significant relationship between premature rupture of membranes and the incidence of leukocytosis in newborns during Caesarean section delivery. A POR of 6.061 indicates that mothers who experience premature rupture of membranes during a Caesarean section have a six-fold higher risk of leukocytosis in their babies. Improving antenatal care and education for pregnant women is essential to reduce the incidence of infection in both mothers and babies.